Technological methods of increasing the durability and resource of working parts of tillage machines - Дудников, Анатолий Андреевич; Беловод, Александра Ивановна; Пасюта, Андрей Григорьевич; Келемеш, Антон Александрович; Горбенко, Александр Викторович (Technology audit and production reserves, 2015)
In this paper we discuss the problem of agricultural engineering is the need to improve the reliability of agricultural machinery based on the use of more efficient technologies both in their manufacture and in the repair industry. The main purpose of research is to study and choice of a method to increase the durability and life of working organs of tillers, taking into account design, technology and material science factors. Analysis of the causes that contribute to the wear rate of the cutting elements working organs of tillers, allows the development process of hardening of details as in their production and recovery. The dynamics of the deterioration of the basic elements of cutting the working bodies of the cultivator wing shares and plowshares. Based on the data developed and put into production technology of hardening of cutting elements working organs of tillers by the vibration deformation. The research results can be used in the manufacture of engineering for hardening of manufactured parts. We have developed a technique using vibration reduction hardening increases the service life and durability of working organs of tillers.